ANALISIS TEKS BAHASA INDONESIA: WACANA KRITIS DALAM WAWANCARA “PERLUASAN AKSES POLITIK KELAS MENENGAH” BENNY HANDOKO DI GREEN RADIO 89,2 FM - Hasian Romadon Tanjung (Jurnal Education and Development, 2021)
Freedom of speech allows one to convey statements to the public. For example, the opinion and appreciation of a person about the political case facing the Indonesian nation today is likely to be self-interest or group. The research was expected to know the views of Benny Handoko about the expansion of middle-class political access in Indonesia. The method of research is qualitative and the object is the discourse. Critical discourse analysis was used to know the truth in the discourse based on the facts delivered, position of social actors, position of ideas, and events placed in the text. Data was collected by analyzing discourse critically based on existing theory. The source of research data is the discourse of the interview "Expansion of Political Access of Middle Class" by Benny Handoko at Green Radio 89.2 Fm on Sunday, May 9th 2010 at 06.00.a.m. Speaker persuaded listeners to recall events that ever happened before to clarify the facts. Benny Handoko has a critical view of the expansion of political access to the middle class in Indonesia. In conveying his ideas and views, he had certain views or values ​​previously believed. The alignment of the discourse was very clear to a problem and a position in the discourse. To know the ideas and views of a person in the discourse, a more in-depth study of the discourse is called critical discourse analysis.